DESENVOLVIMENTO DE FILAMENTOS COMPOSTOS DE PVDF, PLA E HAp PARA IMPRESSÃO DE BIOMATERIAIS ORTOPÉDICOS - OLIVEIRA, PATRICIA CAMARGO DE (2023)
The search for bone substitute biomaterials is a growing demand today, given the increase in life expectancy and quality of life of the population. In this context, investments in the area of biomaterials corresponded to billionaire values in recent years both worldwide and nationally. Calcium hydroxyapatite (HAp) stands out for being bioactive, in such a way that it is already used in several types of biomaterials, mainly those associated with orthopedics and orthodontics. Polymers such as poly(vinylidene fluoride) (PVDF) and poly(lactic acid) (PLA) have been widely studied in biomaterial production area due to their biocompatible properties in contact with living tissues. Above all, PVDF presents piezelectricity when in the β crystalline phase, such an effect favors bone regeneration and is even associated with the natural repair process of this tissue in living organisms. In the present work, the production of composite filaments of PVDF, PLA and HAp in different concentrations and extrusion parameters were studied. Furthermore, the filaments were also applied in a 3D printing technique, in which printing parameters were studied for each piece. Scanning electron microscopy (SEM) images indicate the formation of immiscible polymeric blends for the PVDF and PLA composites. Fourier transform infrared spectroscopy (FTIR) analyzes demonstrate that formation of the β crystalline phase is present in pellets, filaments and printed samples containing PVDF, with emphasis on PVDF/PLA blends. Furthermore, the addition of HAp promotes the bioactivity of the materials, which can be evaluated by SEM and Energy Dispersion X ray Spectroscopy (EDS). In addition, the printed samples with 15% of HAp have a lower contact angle than the PVDF and PLA composites, indicating that the presence of HAp increases in the hydrophilicity of the material.